Factors associated with quality of life measured by EQ-5D in patients with nontuberculous mycobacterial pulmonary disease. - Hong, Ji Young; Lee, Sang A; Kim, Song Yee; Chung, Kyung Soo; Moon, Sung Woo; Kim, Eun Young; Jung, Ji Ye; Park, Moo Suk; Kim, Young Sam; Kim, Se Kyu; Chang, Joon; Kang, Young Ae (Quality of Life Research, 2014)
Purpose: The impact of pulmonary nontuberculous mycobacterial (pNTM) disease on health-related quality of life (HRQoL) has not received significant attention in the literature. In this study, we compared the HRQoL in patients with pNTM disease and healthy subjects and identified influencing factors using EuroQol 5D (EQ-5D) data.Methods: The present study used an age- and sex-matched case-control analysis from a cohort of 85 pNTM patients and 340 participants from a national survey. Baseline EQ-5D utility scores and EQ-5D visual analog scale (VAS) scores were measured in both groups. In patients with pNTM disease, the factors affecting EQ-5D were identified using multiple linear regression analysis.Results: While the median EQ-5D VAS scores were lower in pNTM patients than in the control subjects (pNTM, 70; control, 80; P < 0.001), the median EQ-5D utility scores were similar in two groups (both, 1.000, P = 0.878). Interestingly, the percentage of subjects reporting problems on the anxiety/depression dimension was higher for patients with pNTM disease (18.8 %) compared with the control subjects (11.5 %, P = 0.07). In multivariate analysis, increasing severity of forced expired volume in one second (FEV1) decline was associated with a significant decrease in EQ-5D scores of pNTM patients.Conclusions: This study suggested the EQ-5D may not be useful instrument in pNTM patients due to ceiling effect of EQ-5D and mild disease activity. Patients with pNTM disease tended to report more reduced health status and more problems with anxiety/depression than the healthy controls. Lung function, measured by FEV1, was independently associated with EQ-5D scores in patients with pNTM disease.